WORKSHOP PEMBUATAN MEDIA PEMBELAJARAN CARDBOARD HOOP MULTISIZE BAGI GURU PAUD DI KABUPATEN KARAWANG - Syafrida, Rina; Karyawati, Lilis; Rahayu, Ega Trisna; Permana, Hinggil (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The challenge of implementing learning from home (BDR) during the COVID-19 pandemic at the early childhood level is that the focus of learning is no longer to stimulate 5 aspects of early childhood development but to focus on cognitive aspects. In addition, the BDR phenomenon also results in high screentime activity in children and makes children lazy to do gross motor skills or gross motoric activities. Therefore, an idea emerged from the proposer team through a community service grant to the community of Singapernagsa Karawang University to propose workshop activities for making CB Hoop Multisize learning media in increasing interest in learning in children through activities during the COVID-19 pandemic for PAUD teachers in Karawang Regency. The multisized card board hoop is an innovative learning media in the form of an educational game tool (APE) which has a shape resembling a hula hoop. The novelty of this learning media is that the Multisize CB Hoop is made from used goods in the form of cardboard that is printed to resemble a hula hoop. CB Hoop Multisize has four types of diameter 8, 35, 50 and 70 centimeters. Playing activities that can be done using CB Hoop Multi Size media include jumping, relay running, creeping, throwing, catching and other gross motor activities. This PKM activity was successfully held on November 15, 2020 with 500 participants consisting of early childhood teachers in Karawang Regency.Â